Biodisponibilidade e distribuição tecidual de compostos fenólicos do mirtilo (Vaccinium sp.) obtidos com solvente eutético profundo natural - Silva, Dariane Trivisiol da (2023)
Natural deep eutectic solvents (NADES) are biosustainable solvents proposed as a safe alternative for obtaining bioactive extracts. Despite the low absorption, the phytochemicals widely present in the blueberry, have beneficial effects related to the intestine and brain. However, studies on the in vivo effects of NADES are scarce and their influence on the bioavailability and tissue distribution of phenolic compounds extracted with NADES has not been elucidated. Thus, the objective of this work was to study the pharmacokinetic characteristics and the tissue distribution profile of the bioactive compounds of a biocompatible and ready-to-use blueberry extract obtained with NADES solvent. Rats received (via gavage) a single dose (10.0 mg of polyphenols/kg of body weight) of crude blueberry extract obtained using NADES (EB-NADES) or organic solvent (EB-SORG), the latter being previously dried and reconstituted in water. Non-compartmental pharmacokinetic analysis revealed that EB-NADES increased the bioavailability of anthocyanins by 140% compared to EB-SORG. Compared to SORG, NADES delayed gastric chyme neutralization, increasing the stability of phenolic compounds during in vitro digestion. EB-NADES increased the extent of tissue absorption of anthocyanins by 460% and 17% in the brain and small intestine, respectively, compared to EB-SORG. Furthermore, EB-NADES increased tissue concentrations of phenolic metabolites in the stomach and small intestine. The third stage of this work is described in the appendices and composes the second block of objectives initially established for this Thesis. This step aimed to compare the effect of two antibiotic treatment regimens to induce intestinal dysbiosis and behavioral changes in Wistar rats. The animals were divided into 3 groups: control, cocktail of antibiotics-AB, and vancomycinVAN, which received water or antibiotics by gavage for 10 days (2 mL/kg p.c.). Treatment with AB or VAN reduced the diversity of the intestinal microbiota, through the depletion of Firmicutes phyla and increase of Proteobacteria. AB increased gram-negative bacteria such as Cianobacteria and Desulfobacteria, while VAN reduced Actinobacterota and increased Bacteroidata. Dysbiosis induced by AB or VAN impaired short-term memory, reduced the production of microbial metabolites, dysregulated the immune system, and increased intestinal and blood-brain barrier permeability. Only AB treatment promoted long-term memory damage, parallel to the emergence of pathogenic genera such as Staphylococcus and Curtobacterium, as well as increased the relative abundance of gram-negative microorganisms. AB also promoted complete depletion of microbial metabolites, increased permeability in the hippocampus, and induced immune system dysregulation to a greater extent than VAN. Taken together, the data from the first block of this Thesis indicate that NADES can be used as a ready-to-use vehicle or solvent extractor to enhance plasma and tissue absorption of blueberry phenolic compounds. In addition, we concluded in the second step that the microbiota and its metabolites play an important role in cognitive impairment and that the differences between AB and VAN may be linked to the type of microbiota affected, since the treatment regimens have different bacterial targets.